Guillain-Barré syndrome following chickenpox: a case series. (3rd May 2016) - Tatarelli, P.; Garnero, M.; Del Bono, V.; Camera, M.; Schenone, A.; Grandis, M.; Benedetti, L.; Viscoli, C.
Abstract : Guillain–Barré syndrome (GBS) is an acute, immune-mediated polyradiculoneuropathy, usually triggered by an infectious episode, mostly of viral origin. Varicella zoster virus (VZV) is a rare cause of GBS, mainly in the case of latent infection reactivation. We report on three adult patients who developed GBS following chickenpox, after a short period of latency. They were promptly treated with intravenous immunoglobulin, and the first one with plasma exchange additionally. All the patients experienced almost complete clinical recovery. Our experience suggests that primary VZV infection constitutes a GBS triggering event.